A Rare Case of Squamous Cell Carcinoma arising in Mature Cystic Teratoma - Adhikari, Alisha; Sharma, Prashim; Singh, Mrinalini; Yadav, Nitesh (Birat Journal of Health Sciences, 2024)
Squamous cell carcinoma (SCC) arising within a mature cystic teratoma (MCT) is a rare neoplasm. Though it is a malignant tumour, it can remain clinically silent. On radiologic examination we can detect the size, extent of the tumour and whether it is cystic or solid neoplasm. To diagnose malignancy histopathologic examination is needed in most of the cases. We report a case of a 65-year-old female presenting with a left pelvic mass. The mass was radiologically suggestive of mature cystic teratoma. However on histopathology it was diagnosed as squamous cell carcinoma arising in a mature cystic teratoma. This case underscores the importance of considering malignant transformation in seemingly benign ovarian masses and emphasises the challenges in diagnosis, treatment and prognosis associated with this rare occurrence.